Лінгвофразеологічна інтерпретація концепту сім'я як духовної цінності в поетичному світі Віктора Бойка - Черненко, Ольга Ігорівна (Ужгородський національний університет, 2020)
У статті з'ясовано місце та значення концепту СІМ'Я в поетичному світі Віктора Бойка, зроблено спробу дослідити сімейні цінності крізь призму фразеології української мови й проаналізувати принципи, на яких базується родина. Визначено значення концепту СІМ'Я як одного з пріоритетних аспектів аксіологічної науки, а також досліджено мікроконтексти поетичних текстів митця, у яких цей ціннісно-лінгвістичний аспект набуває найяскравіших ознак. Проаналізовано складники концепту СІМ'Я, виокремлено напрямки розвитку цього поняття. А також зосереджено увагу на характеристиці духовних цінностей особистості, подано найпереконливіші класифікації вчених щодо їхнього існування. Запропоновано мікроконтексти, у яких найглибше можна виокремити основні риси концепту СІМ'Я, обґрунтовано ідіостильову й філософську картини світу В.С. Бойка, відповідні риси його мовної картини світу. Сімейні цінності – це визначені суспільством норми й постулати, на яких базується, а також принципи, яких дотримується, родина. Формування поняття духовні цінності разом із сімейними відбувалося протягом багатьох століть не лише в соціумі, але й в українській лінгвокультурі. Окрім того, родина належить до базових духовних цінностей людини. Родинні мотиви наявні в народній творчості: піснях, легендах, казках, прислів'ях тощо, а також є актуальними для літературної діяльності. Відповідно цей концепт є універсальним і регулярно вербалізується низкою лексем. Використання автором художніх засобів робить мову його творів виразною й точною. Влучні метафори або цікаві порівняння виокремлюють лірику Віктора Бойка з-поміж творів інших митців. Макроконцепт СІМ'Я є важливим складником будь-якої лінгвокультури, адже протягом багатьох століть чи навіть тисячоліть родинні зв'язки були найменшою державною ланкою. Родина посідала чи не найперше місце серед усіх ціннісних орієнтирів індивіда. Серед багатьох інтенцій, у яких вербалізується концепт СІМ'Я, виділяємо такі художньо-семантичні смисли, у яких він реалізується: родина – близькі родичі, родина – пам'ять, родина – війна, родина – захист від негараздів, родина – думки, родина – щастя, любов, родина – кохання, родина – рідний край.

The article clarifies the place and significance of the concept of FAMILY in the poetic world of Viktor Boyko, as well as attempts to explore family values through the prism of the Ukrainian language and analyze the principles on which the family as such is based. Identify the importance of the concept of FAMILY as one of the priority aspects of axiological science, as well as explore the micro-contexts of poetic texts of the artist, in which this valuelinguistic aspect acquires the brightest features. In Ukrainian linguistics, the concept of moral values in the minds of native speakers was formed over many centuries and influenced by the Christian faith, the teachings of prominent educators, teachers, philosophers, public figures who promoted humanistic ideals, proclaiming the importance of human existence. In modern linguistic space, the concept of FAMILY has attracted the attention of such scholars as A. A. Ryzhkina, who directed the vectors of her research on the etymological analysis of the concept of FAMILY in Chinese; K. V. Korotych with the study of changes in the concept of FAMILY that took place in Soviet times. The work of V.B. Yakovleva, who in her dissertation analyzed the linguistic expression of the representatives of the concept in the Ukrainian language picture of the world, defined the composition of the lexical-semantic group of families as the main exponent of the concept of the same name, tracing changes in synchronic and diachronic aspects. In modern scientific studies, there is no consensus among scholars on the classification of moral values, although all are convinced that they belong to the phenomena of human consciousness and find expression in the most important landmarks: norms, ideals, feelings, etc. that determine the development of an individual or ethnic community. humanity as a whole. Despite the seeming simplicity of the concept of moral values, to determine what are such values for a particular linguistic personality seems not so easy. Moral values are contrasted with material values, and the epithet moral indicates the connection of values with the inner world of man. National values are those parameters that are important for each individual nation. This group includes ethnic concepts, those realities that are marked for a particular people. For example, for Ukrainians such concepts are KALУNA, TRУZUB, KOZAK, UKRAINE, VYSHYVANKA, etc.; for a Russian, the concepts representing national values will be BIRCH, BEAR, RUSSIA, etc.; Japanese national values will be reflected in the concepts of HOKKU, KIMONO, TYADO, etc. Family values are the principles on which the family is based. These include the concepts of LOVE, CHILDREN, HUSBAND, WIFE, FATHER, MOTHER, SISTER, HOME, DОBROBUT, FAITHFULNESS and many other realities, one way or another related to family life. The FAMILY macroconcept is an important component of any linguistic culture, as for many centuries or even millennia, family ties have been the smallest part of government. As a product of a particular social system, the family reflects the state of development of this system, affects the life and work of each individual member of the community, and can acquire symbolic significance, reflecting the moral heritage of the people, its worldview. In addition, the family belongs to the basic moral values of man. Family motives often appear in folk art: songs, legends, fairy tales, proverbs, etc., and are also relevant to literary activity. Accordingly, this concept is universal and is regularly verbalized by a number of tokens.
Linguistic and phraseological interpretation of the concept family as a moral value in the poetic world of Viktor Boyko
Keywords: моральні цінності; аксіологічна наука; лінгвістика; фразеологія; moral values; axiological science; linguistics; phraseology